2018
DOI: 10.1021/acs.chemrev.8b00158
|View full text |Cite
|
Sign up to set email alerts
|

The Many “Facets” of Halide Ions in the Chemistry of Colloidal Inorganic Nanocrystals

Abstract: Over the years, scientists have identified various synthetic “handles” while developing wet chemical protocols for achieving a high level of shape and compositional complexity in colloidal nanomaterials. Halide ions have emerged as one such handle which serve as important surface active species that regulate nanocrystal (NC) growth and concomitant physicochemical properties. Halide ions affect the NC growth kinetics through several means, including selective binding on crystal facets, complexation with the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
248
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(253 citation statements)
references
References 466 publications
(1,160 reference statements)
3
248
0
2
Order By: Relevance
“…Since mercury has a strong affinity with thiols, a short thiol (ethanedithiol or mercapto alcohol) was used as a transfer agent to disperse the nanocrystals in the polar phase solvent dimethyl formamide (DMF) from the initial toluene solvent. The addition of HgCl 2 was found to further enhance electronic passivation and allowed good conductivity . We observed that the nanoparticle spectrum was barely affected by this ligand exchange procedure, see Figure b.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Since mercury has a strong affinity with thiols, a short thiol (ethanedithiol or mercapto alcohol) was used as a transfer agent to disperse the nanocrystals in the polar phase solvent dimethyl formamide (DMF) from the initial toluene solvent. The addition of HgCl 2 was found to further enhance electronic passivation and allowed good conductivity . We observed that the nanoparticle spectrum was barely affected by this ligand exchange procedure, see Figure b.…”
mentioning
confidence: 80%
“…The addition of HgCl 2 was found to further enhance electronic passivation and allowed good conductivity. [25,[36][37][38] We observed that the nanoparticle spectrum was barely affected by this ligand exchange procedure, see Figure 1b. This contrasts with the solid state ligand exchange (SSLE) based on ethanedithiol (EDT) which led to a redshift and broadening of the band edge transition.…”
mentioning
confidence: 99%
“…Considering 119 Sn MAS‐NMR and XPS data, showing that clay stabilized the formation of defective SnO 2 nanocrystals displaying a higher number of undercoordinated surface Sn 2+ atoms, we believe that these defects act as strong Lewis acid sites (Scheme e). Undercoordinated surfaces sites of nanocrystals are electron deficient and are known to display a Lewis‐acidic character . Thermal treatment of Sn‐MMT would cause sintering of the SnO 2 nanocrystals and migration of H + inside the clay.…”
Section: Resultsmentioning
confidence: 99%
“…Undercoordinated surfaces sites of nanocrystals are electron deficient and are known to display a Lewisacidic character. [58] Thermal treatment of Sn-MMT would cause sintering of the SnO 2 nanocrystals and migration of H + inside the clay. The resulting catalyst would contain neutral SnO 2 nanocrystal devoid of its acidity.…”
Section: Discussion On the Nature Of The Active Sitementioning
confidence: 99%
“…近年来, 光催化材料由于其在光照下可以去除水 溶性污染物而备受关注 [88] . 其中, 二氧化钛(TiO 2 )由于 其无毒、化学稳定的特性, 被认为是降解有机污染物 方面最理想光催化材料之一 [89] . 然而, 由于TiO 2 光生电 子-空穴对容易重组, 并且其带隙较宽, 导致其光催化性 能十分有限 [90] , 限制了其在水处理方面的进一步应用.…”
Section: 自清洁性能unclassified